2014
DOI: 10.4172/2155-9562-5-1000219
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mesenchymal Stem Cells in the Treatment of Multiple Sclerosis: An Overview of Open Labels and Ongoing Studies

Abstract: Multiple sclerosis (MS) is a demyelinating disease of unknown etiology that affects the Central Nervous System (CNS) where autoimmune-mediated mechanisms are thought to be at work. There are two possible options for treating MS, to prevent damage, and to repair the already impaired CNS. Stem Cells (SC) therapy emerges as a potential new hope for MS patients as it could accomplish both functions. There is a growing body of literature that supports the potential of the SC for immunomodulation and re-myelination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, most trials were under-reported due to the low number of treated subjects, different dosages [3] used in the studies, the feasibility of autologous [12] or allogenic transplantation [3], and the unclear therapeutic window after the treatment effect. Several human clinical trials have reported a favorable safety profile on transplantation of these multipotent stem cells [13,14]. While the safety of using MSCs in the treatment of diseases such as hematological, cardiac, and inflammatory diseases has been extensively documented, there is limited research available regarding their application in the context of MS [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most trials were under-reported due to the low number of treated subjects, different dosages [3] used in the studies, the feasibility of autologous [12] or allogenic transplantation [3], and the unclear therapeutic window after the treatment effect. Several human clinical trials have reported a favorable safety profile on transplantation of these multipotent stem cells [13,14]. While the safety of using MSCs in the treatment of diseases such as hematological, cardiac, and inflammatory diseases has been extensively documented, there is limited research available regarding their application in the context of MS [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several human clinical trials have reported a favorable safety profile on transplantation of these multipotent stem cells [13,14]. While the safety of using MSCs in the treatment of diseases such as hematological, cardiac, and inflammatory diseases has been extensively documented, there is limited research available regarding their application in the context of MS [14]. Hence, the utilization of MSCs as an alternative therapeutic approach for managing the progression of MS is garnering growing interest [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MSCs have shown efficacy in the treatment of the MS animal model, experimental autoimmune encephalomyelitis (EAE), by modulating the activity of dendritic cells and T cells [12,14,15]. Moreover, recent reports suggest that MSCs can be used to reduce autoimmune inflammation in MS patients [16,17]. However, their postinfusion potency is unpredictable [14,15], raising the need for safe and scalable bioengineering approaches to further maximize the therapeutic potential of MSCs in the context of MS.…”
Section: Introductionmentioning
confidence: 99%